Peran Orang Tua Dalam Proses Pembelajaran Jarak Jauh Anak Kelas Rendah SDN Bontorannu 1 Kecamatan Mariso - Adil Awal; Nunu Verbrian; Ajeng Tryana; Marina Nurdin; Nurul Hikmah; Puri Magfirah (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to determine the role of parents in distance learning in low-grade children at SDN Bontorannu 1, Mariso District, Makassar City by using a qualitative research type and using a case study approach. Data collection techniques used are observation, interviews, and documentation. The results showed that the role of parents in distance learning includes several aspects. Parents as facilitators prepare distance learning media that support children's needs, parents as companions and mentors guide in doing school assignments. The results of the study also show that there are obstacles that hinder distance learning, namely insufficient time to accompany children in the learning process because they have to work, lack of understanding of learning materials by parents, the ability to provide and operate mobile phones as learning media. Based on the results of the study, it was obtained that suggestions, especially for the government, were expected to be used as a benchmark in determining policies in the field of education, and suggestions for parents were expected to provide information to parents as educators in the family, especially in the process of distance learning assistance.